Electric Grid Vulnerabilities to Rising Air Temperatures in Arizona. (2016) - Burillo, Daniel; Chester, Mikhail; Ruddell, Benjamin
Abstract: Ambient air temperatures are expected to increase in the US desert southwest by 1-5 °C mid-century which will strain the electric power grid through increased loads, reduced power capacities, efficiencies, and material lifespans. To better understand and quantify this risk, a power infrastructure failure model is created to estimate changes in outage rates of components for increases in air temperatures in Arizona. Components analyzed include generation, transmission lines, and substations, because their outages can lead to cascading failures and interruptions of other critical infrastructure systems such as water, transportation, and information/communication technology. Preliminary results indicate that components could require maintenance or replacement up to 3 times more often due to mechanical failures, outages could occur up to 30 times more often due to overcurrent tripping, and the probability of cascading failures could increase 30 times as well for a 1 °C increase in ambient air temperature. Preventative measures can include infrastructure upgrades to more thermal resistant parts, installation of cooling systems, smart grid power flow controls, and expanding programs for demand side management and customer energy efficiency.